2018
DOI: 10.1002/ar.23741
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the Long Head of the Triceps Brachii in Humans—A Fresh Look

Abstract: The triceps brachii muscle occupies the posterior compartment of the arm in humans and has three heads. The lateral and medial heads originate from the humerus and the long head arises from the infraglenoid tubercle of the scapula. All heads form a common tendon that inserts onto the olecranon and the deep antebrachial fascia on each side of it. Each head receives its own motor branch, which all are thought to originate from the radial nerve. However, several studies reported that the motor branch of the long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…Therefore, preoperative electromyography should include the LHT to confirm whether the nerve to the LHT could be a proper donor for nerve transfer. Although we did not find any axillary‐innervated variation of LHT in 37 cadaveric shoulders, our results contribute to the published data and support the use of the nerve to the LHT as a nerve transfer donor 8,9,20,25 …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Therefore, preoperative electromyography should include the LHT to confirm whether the nerve to the LHT could be a proper donor for nerve transfer. Although we did not find any axillary‐innervated variation of LHT in 37 cadaveric shoulders, our results contribute to the published data and support the use of the nerve to the LHT as a nerve transfer donor 8,9,20,25 …”
Section: Discussionsupporting
confidence: 74%
“…The motor branch of the LHT arises from the radial nerve in the major anatomy textbooks, 1,2 but some cadaveric studies and case reports have shown that it is innervated by the axillary nerve 8‐10 . A recent review by Wade et al summarized that at maximum, 14% of specimens (47 of 330) in the literature reportedly have axillary‐innervated LHT, although this result should be carefully interpreted taking publication bias into account 20 . The axillary‐innervated variation of LHT has two clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…The TB-Med is located at the deeper region, the fleshy origin is along the posterior humerus between the insertion of the teres major muscle and the olecranon fossa. The TB-Lat and TB-Long are located superficially, originating from the posterior surface of the superior humerus and infraglenoid tuberosity of the scapula, respectively, with two tendons at the proximal and distal ends [ 21 , 22 ]. All three heads of the TB insert by a common, broad tendon into the posterior surface of the olecranon and into the deep antebrachial fascia on each side of it [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first contribution of this special issue is an anatomical investigation of the shoulder musculature by Michael Wade and colleagues from the Ziermann lab (Howard University College of Medicine) which provides a fresh look at our understanding of the innervation of the three heads of the triceps brachii in humans (Wade et al, , this issue). It is generally assumed that the motor innervation of the triceps brachii muscle originates from the radial nerve—indeed the standard teaching in gross anatomy is that the radial nerve innervates all of the muscles of the posterior compartment of the arm and forearm, though some studies contradict this assumption finding that the innervation of long head of the triceps (LHT) arises from the axillary nerve or directly from the posterior cord (De Sèze et al, ).…”
mentioning
confidence: 99%
“…It is generally assumed that the motor innervation of the triceps brachii muscle originates from the radial nerve—indeed the standard teaching in gross anatomy is that the radial nerve innervates all of the muscles of the posterior compartment of the arm and forearm, though some studies contradict this assumption finding that the innervation of long head of the triceps (LHT) arises from the axillary nerve or directly from the posterior cord (De Sèze et al, ). By dissecting 27 human triceps, Wade et al () found that the LHT is always innervated by the radial nerve. The authors also conducted a literature review where they found that in some cases the innervation of LHT is by the axillary nerve and suggested that the different methodologies used may create confusion in the results.…”
mentioning
confidence: 99%